Family Business and Transgenerational Model for Policy Development of Community Tourism Business and Entreprenuership - Talib, Azlizan; Yusoff, Mohd. Nazaruddin; Sharif Ali, Sharif Shofirun; Abd Rahman, Muhamad Azwan; Ismail, Hairul Nizam; Misnan, Siti Hajar (Universiti Utara Malaysia, 2022)
Entrepreneurship is an activity that brings benefits through profit-oriented business development. In family business grows and develops with two main aspects, business and family. While, tourism business creating a wide range of tourism related products [a] attractions and activities, [b] accommodation, [c] transportation, [d] tourism facilities and [e] training institutions in tourist destinations. Thus, this study will identify the opportunities and constraints of the family business sector in the tourism industry according to the four main dimensions of the family business sector, namely micro -business transgeneration, social infrastructure in family business, physical / technical infrastructure and energy consumption level. By using questionnaire, 67 entrepreneur in business tourism has been analyse using correlation and regression. Result shown that family relationship, social infrastructure and energy usage are at satisfactory level. Only physical/ technical infrastructure provided by the government is at unsatisfactory level. Hence, this study can act as a guide in formulating new policies or improving existing policies in ensuring the sustainability of family businesses in the tourism sector.